Pembuatan Logo Dan Label Sebagai Branding Produk Pada UMKM Di Kelurahan Sentul - Kurnia Yuli Sintakarini; Ririt Iriani Sri Setiawati; Mohammad Wahed (Fakultas Teknik Universitas Cenderawasih, 2023)
Product branding plays a very important role in running a business, because business branding is a form of marketing and product recognition in business activities carried out by business actors in order to expand their product market. The branding also serves as a benchmark that the resulting product can be said to be feasible, valid and ongoing. The problem that is often encountered in the surrounding community, especially Micro, Small and Medium Enterprises (MSMEs) is an understanding of the importance of having qualified product branding and how to create branding for their businesses causes them not to have product branding. Therefore this service activity aims to provide understanding to the community in the form of outreach about what product branding is and provide assistance in terms of making product branding, especially for business actors in the Sentul sub-district area. The method implemented in this mentoring activity was divided into three stages, in the first stage we conducted surveys and interviews regarding product branding that had been owned by business actors in the Sentul village, the next stage was conducting socialization activities regarding the importance of having product branding and the final stage is to provide assistance in making logos and labels. The results obtained by this activity were an increase in the understanding of business actors in the Sentul sub-district regarding the importance of having product branding.